Authentic spatial vulnerability assessment for evacuation shelters in disaster planning: A case study of Tubay, Agusan Del Norte, Philippines - Cauba, Arturo; Morales, Raeanna Kristine; Jovellar, Cecil (Institute for Advanced Science Social, and Sustainable Future, 2024)
Authenticity plays a pivotal role in addressing the primary challenges encountered in disaster planning, particularly when it comes to assessing vulnerability and evaluating the spatial distribution of shelter demand and resources. Ensuring the accuracy and reliability of data is essential for effectively managing available resources at each evacuation center, as well as for accommodating evacuees and ensuring the safety of both staff and refugees. In real-life circumstances, the authenticity of the information gathered becomes even more critical, as an imbalance in shelter and population distribution often hinders access to evacuation shelters. In this paper, the researchers introduce a spatial assessment technique that not only analyzes vulnerability but also authentically assesses the spatial distribution of shelter demand and supplies, thereby enhancing the overall effectiveness of disaster planning in Tubay, Agusan del Norte, Philippines. The study focuses on Tubay, Agusan del Norte, Philippines, taking into account spatial accessibility. The researchers found that out of the 33 shelters assessed, 21 are feasible locations for evacuation centers, and approximately 51% of the total population points are vulnerable to flooding. Utilizing GIS maps, the results reveal a significant decrease in overall shelter capacity to 64.26%. The study's findings emphasize the critical need for evaluating the relationship between vulnerable shelters and the demand for resources at each location. This information serves as a practical tool, offering flexibility in terms of data availability for decision-makers, enabling them to investigate areas, and providing a valuable reference for developing and improving emergency management decisions and strategies.